PENGARUH WORK-LIFE BALANCE GENERASI MILENIAL TERHADAP OCB: PERAN PEMEDIASI KEPUASAN KERJA - Annisa Fajri (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of work-life balance and job satisfaction on Organizational Citizenship Behavior (OCB). Respondents are employees of the millennial generation throughout Indonesia. The sample is 107 respondents, taken by purposive sampling technique. PROCESS Macro method is used as a data analysis technique with SPSS 22.0 application. Based on the research, it was found that work-life balance has a positive and significant effect on and OCB, and job satisfaction mediates the effect of work-life balance on OCB significantly. In conclusion, OCB coaching to create a millennial generation is very important to produce better performance. Overall, this research provides a significant contribution to the development of research in the field of human resource management and organizational behaviour in the field of millennial employees throughout Indonesia.